Meningkatkan Mutu Pendidikan Melalui Evaluasi Komprehensif Program Pendidikan di MAS Al-Washliyah Kecamatan Medan Amplas Kota Medan - Mukhlasin, Ahmad; Tambusai, Rina Hidayah; Fuadi, Wan Anwar; Halim, Abdul (LPPPI Publishing, 2024)
Educational quality is a complex and multifaceted issue. This study aims to comprehensively evaluate the education program at MAS Al-Washliyah using the CIPP (Context, Input, Process, Product) model to improve educational quality. This study employs a qualitative research method with a case study approach. Data collection techniques include interviews, observations, and documentation. Thematic data analysis is used to analyze the data. The findings reveal that the education program at MAS Al-Washliyah has made some progress, but there are still several obstacles that need to be addressed. Recommendations made in this study are to strengthen the role of stakeholders, improve the quality of teachers and education personnel, provide adequate facilities and infrastructure, and increase community participation in education programs.